Konstruksi Identitas Kolektif Warga Desa Adat dalam Gerakan Tolak Reklamasi Teluk Benoa di Bali - I Made Anom Wiranata; Hotman Siahaan (Jurnal Kajian Bali (Journal of Bali Studies), 2019)
The collective identity as customary village members in Bali has played a significant role in creating consistency of the movement to reject the Benoa Bay reclamation project. This article aimed to study the construction of the collective identity of the customary village members in Bali. By using a qualitative research method with a phenomenological approach, this study examines the structure of awareness of the subjects concerning the phenomenon of the movement rejecting the Benoa Bay reclamation plan. This research finds that the collective identity of the customary village in Bali in opposing Benoa Bay reclamation occurred through a process of construction among social movement actors both in latent dimension (daily activities) and visible dimension through collective actions. The construction of the collective identity of the customary village members involved elements of cognition, affection or emotion, as well as social relations both in the internal movement groups, as well as with external parties. Keywords: Benoa Bay reclamation project, collective identity, customary village, social movement.